Women on the Steering Wheel: Identifying the Potentials of Women in Improving the Protection of Indonesian Women Migrant Workers - Yazid, Sylvia; Dewi, Elisabeth (JAS (Journal of ASEAN Studies), 2015)
This paper is based on a research that looked into the potentials of women as stakeholders in improving the protection of Indonesian women migrant workers abroad. It was designed based on the assumptions that an identification of the potentials of women at various levels and in various institutions may positively contribute to the efforts of finding solutions for the problems faced by women migrant workers and that rather than being seen merely as victims, women should be seen as actors who can actively participate in addressing the problems. This paper analyzes efforts made by a number of Indonesian women who are publicly recognized for their works in promoting the protection of Indonesian women migrant workers, both as state and non-state actors in the context of policy making. The focus is on how these women perceive the extend to which their efforts have been able to influence the policy making process. The discussion also includes how the women responded to the challenges and opportunities that they encounter as part of their learning process. The data for this paper was gathered through interviews with six prominent woman figures who are known for their work on the issue of women migrant workers. While confirming that as actors outside the government these women have made efforts to influence the policy making process, this paper showcases that the actual impact of their efforts is highly determined by the policy environment.